A frequency adaptive multiple complex coefficient filter for grid connected applications - Boumediene, Bachir; Araria, Rabah; Chedjara, Zakaria; Mekhloufi, Belkacem; Bey, Mohamed; Wira, Patrice (Bulletin of Electrical Engineering and Informatics, 2024)
In the realm of synchronization techniques, the dichotomy between open loops (OLSs) and closed loops (CLSs) presents a perennial challenge: how to enhance dynamic performance without sacrificing stability and disturbance rejection. While OLS techniques offer rapid dynamic response and unwavering stability, they often falter in non-nominal frequency scenarios. Conversely, CLS techniques grapple with the delicate balance of bolstering dynamic performance while maintaining robust stability. To surmount these obstacles, this study proposes an innovative approach: the integration of a frequency locked loop (FLL) as a secondary frequency detector within synchronization structures, coupled with the multiple-complex coefficient-filter (MCCF). This amalgamation bestows notable advantages. Firstly, from a control perspective, the resultant synchronization technique resembles a quasi-OLS, obviating the need for intricate stability analyses. Moreover, it exhibits commendable disturbances rejection alongside swift dynamic response. Through comprehensive simulation, our proposed technique showcases superiority over existing counterparts, evidencing enhanced settling time, disturbances rejection, and efficiency in the face of frequency drifts.